Temptation and Intimidation in the Holy Quran and the Sunna And their Teaching - learning Perspectives - الدكتورة ساھرة عبد الله ضاحي (College of Education for Women, 2019)
Methods of teaching plays an important vole in the educational process because is the link between the teacher and the learner. The process of teaching doesut fulfill the desirable results unless the methods of guiding and teaching are provided and through a qualified educationalist capable of communicating the syllabus to the students in an easy and clear way. In spite of the diversity of the methods of teaching ,there is no one way suitable for all the educational purposes , all the sciences ,all the subjects ,all the levels of growth ,levels of teaching, maturity and intelligences ,all teachers and educationalists and all the circum stances surrounding the teaching processes .The teacher is the one who chooses the method that suits the educational purpose to achieve, the subjects he teacher ,the kind of lesson ,the level of growth and learning ,level of maturity ,intelligence and achievement of his students, the available requirements .when we talk about the methods of teaching Islamic Education we have to talk about the first educationalist our prophet Muhammad who did handle the process of education and teaching as he was ordered by Almighty God who says (( My God ordered me to teach you what you are ignorant of from what he has taught me)). The researcher in this study sheds light on one style of education which has already been mentioned many times in the Holy Quran and the Sunnite of our prophet which is through the method of temptation and intimidation. The aim of the present study is to indemnify out he two styles temptation and intimidation in the Holy Quran and the Sunni and their pedagogical - learning perspectives. To achieve this aim, the researcher used the analytical descriptive method to account for the number of uses in the Holy Quran and the sunna by calculating the repeated words that carry in meaning and pronunciation the meaning of temptation and intimidation. The researcher has reached into the following conclusions: 1- The most repetitive verses in the Holy Quran for the temptation in which "paradise "is used are about (113). 2- The most repetitive verses for the intimidation in which "fear " in used are about (121). 3- As for the Sunna, the temptation saying for the "prayer" comes on the top of the list, about (374). 4- While the intimidation in literature include about (230). The researcher suggested dictating the two styles in the college teaching. Also the researcher suggested the following recommendations : 1- Holding training courses for the teacher of Islamic education to know such styles and how to teach them . 2- Making use of the prophets teaching styles in educating his followers and putting them on the right track including the implantation of the right principles for the students. 3- Shedding light on the influence of the tow styles in teaching the college students. 4- Identifying the influence of other styles of the prophet on other stages.